Assessing Structural Geological Controls on Groundwater Processes in Mountain Settings: Insights From Three‐Dimensional Numerical Modeling - Marti, Etienne (2025)
Mountains play a critical role in the hydrological cycle by transferring heavy precipitation to lowland aquifers. However, their complexity and remoteness limit our understanding of groundwater flow, particularly the influence of faults. To fill the gap, semi-idealized 3D numerical models calibrated using the mountain river network and the lowland piezometric gradient were developed. The impact of faults on groundwater flow was explored by varying their hydraulic conductivity, position, orientation, and length. The metrics evaluated were flow partitioning, seepage area, flow path lengths, and residence times. It was found that the hydraulic conductivity contrast between a fault and the pervasive rock controls recharge partitioning as much as the overall transmissivity of the pervasive rock. Regional conductive faults parallel to the orogen promote mountain-block recharge over surface flow, as significantly as thick systems do, and vice versa. Local-scale faults can exert as much influence as regional faults when crossing the catchment outlet, highlighting the importance of local heterogeneity in regional flow dynamics. Intercatchment flow is primarily governed by lithology and topography and is modulated by the fault position relative to major topographic features. Faults influence seepage areas within a multi-kilometer distance in characteristic patterns useful for segregating their effective role. By lowering the water table, conductive faults systematically reduce the seepage areas. Meanwhile, barriers decrease seepage areas downstream of their trace and increase them upstream, without affecting the extent of seepage. Finally, the distributions of flow path lengths and residence times are uncorrelated, highlighting the importance of numerical modeling for groundwater dating.